Vigilance behaviour of small cervids in South-West Finland: effects of group size, time of day and predation risk in an agricultural landscape - Kari, Iina (My University, 2025)
This master’s thesis examines the vigilance behaviour of white-tailed deer (Odocoileus virginianus) and roe deer (Capreolus capreolus) in agricultural landscapes in South-West Finland. The aim of the study was to investigate how potential predator (gray wolf, Canis lupus) presence, group size, time of day, and the distance from forest cover affect the vigilance of foraging deer. The main hypotheses were that 1) deer in areas with higher predation risk (wolf presence) were expected to show increased vigilance as an adaptive response to the potential threat posed by predators; 2) vigilance was expected to decrease with increasing group size due to collective detection shared with group members; and 3) deer foraging farther from forest edge were expected to be less vigilant. The data were primarily collected by using video monitoring during May and June 2024. The influence of wolves was assessed by comparing vigilance-related variables in white-tailed deer observed within core areas of wolf territories (high predation risk/wolf present) and at the edges or outside the illustrated territory boundaries (low predation risk /wolf absent). Interspecific comparisons were conducted only with data from low-risk areas, as roe deer were too rarely observed within high-risk areas to be included in all analyses. During observation bouts, vigilance was measured as 1) the relative proportion of the time an animal was vigilant, 2) the number of vigilance bouts during a fixed observation period, and 3) the average duration of vigilance bouts. The data were analysed using generalized linear mixed models. The results showed that wolf presence did not increase vigilance in white-tailed deer, as hypothesised. No statistically significant effect was found in foraging distance to nearest forest edge. Instead, group size and time of day were the key predictors: vigilance decreased in larger groups and was highest during twilight hours compared to nighttime. Vigilance frequency was also significantly lower in May than June in white-tailed deer. In the interspecific comparisons, no statistically significant effects were found between the species in any vigilance-related variables. However, in low-risk areas the average vigilance bout duration was influenced by observation month across both species, with bout durations being shorter in June compared to May. These findings suggest that in human-modified landscapes, social and temporal factors may shape the vigilance behaviour of small cervids more than predator presence. Future research should also consider individual-level traits, interspecific competition, and the effects of human disturbance, such as hunting season, on deer vigilance.

Tämä pro gradu -tutkielma tarkastelee valkohäntäkauriin (Odocoileus virginianus) ja metsäkauriin (Capreolus capreolus) valppauskäyttäytymistä Lounais-Suomen maatalousalueilla. Tutkimuksen tavoitteena oli selvittää, kuinka pedon (susi, Canis lupus) mahdollinen läsnäolo, ryhmäkoko, vuorokaudenaika sekä etäisyys metsän reunasta vaikuttavat pelloilla laiduntavien kauriseläinten valppauteen. Tutkimuksen keskeisten hypoteesien mukaan 1) kauriiden oletettiin olevan valppaampia alueilla, joilla saalistusriski on suurempi ja suden läsnäolo todennäköisempää, 2) valppauden oletettiin vähenevän ryhmäkoon kasvaessa, koska ryhmän jäsenet jakavat tarkkailuvastuun, ja 3) kauempana metsän reunasta laiduntavien yksilöiden oletettiin olevan vähemmän valppaita. Aineisto kerättiin pääosin videohavainnoinnin avulla touko-kesäkuussa 2024. Suden epäsuoraa vaikutusta ruokailukäyttäytymiseen arvioitiin vertaamalla valkohäntäkauriiden valppausmuuttujia susireviirien ydinalueilta (korkeampi saalistusriski/susi läsnä) sekä reviirien raja-alueilta tai niiden ulkopuolelta (matalampi saalistusriski/susi ei läsnä). Lajien välistä vertailua tehtiin vain matalan saalistusriskin alueiden havainnoista, sillä metsäkauriita ei havaittu riittävästi susireviirien sisäpuolella kerätyssä tutkimusaineistossa. Valppautta mitattiin tarkkailujaksojen aikana kolmella tavalla: 1) valppausajan suhteellisena osuutena tarkkailuajasta, 2) valppausjaksojen lukumääränä sekä 3) valppausjaksojen keskimääräisenä kestona. Aineisto analysoitiin yleistetyillä lineaarisilla sekamalleilla. Tulokset osoittivat, ettei suden läsnäolo lisännyt valkohäntäkauriiden valppautta hypoteesin mukaisesti. Myöskään etäisyydellä metsän reunasta ei havaittu tilastollisesti merkitsevää vaikutusta. Sen sijaan lauman ryhmäkoko ja vuorokaudenaika olivat keskeisiä selittäjiä: suuremmissa ryhmissä valppaus väheni ja oli suurimmillaan hämärän aikaan verrattuna yöhön. Valkohäntäkauriin valppausjaksojen määrä oli myös merkitsevästi pienempi toukokuussa kuin kesäkuussa. Lajien välisessä vertailussa matalan saalistusriskin alueilla ei havaittu tilastollisesti merkitseviä eroja lajien valppauskäyttäytymisessä. Havainnointikuukausi vaikutti valppausjaksojen keskimääräiseen kestoon molemmilla lajeilla siten, että jaksot olivat lyhyempiä kesäkuussa kuin toukokuussa. Tulokset viittaavat siihen, että ihmistoiminnan muovaamassa ympäristössä sosiaaliset ja ajalliset tekijät voivat vaikuttaa pienten hirvieläinten valppauskäyttäytymiseen enemmän kuin petojen läsnäolo. Tulevissa tutkimuksissa tulisi tarkastella laajemmin myös yksilötason muuttujia, lajien välistä kilpailua sekä ihmistoiminnan, kuten metsästyskauden, vaikutuksia eläinten valppauteen.
Keywords: vigilance behaviour, indirect effects of predators, predation risk, ecology of fear